Effect of Xingbi Gel Nasal Drops on Rats with Allergic Rhinitis Based on the Nasal Mucosa-Hippocampus Neuroimmune Mechanism - FAN Xueqi; QIU Caixia; YAN Shuiping; ZHUANG Xiangli; AI Si; GUO Lihua; ZHENG Jian (康复学报)
ObjectiveTo explore the effect of Xingbi gel nasal drops on rats with allergic rhinitis (AR) based on the nasal mucosa-hippocampus neuroimmune mechanism.MethodsA total of 40 SPF SD rats at postnatal day 21 (PND21) were randomly divided into normal group, model group, traditional Chinese medicine group and western medicine group, with 10 cases in each group. Except for the normal group, the other three groups were sensitized by ovalbumin (OVA) to establish AR animal models. After the model was successfully established, the normal group and model group were both given normal saline nasal drops (50 μL once), the traditional Chinese medicine group was given Xingbi gel nasal drops (50 μL once), and the western medicine group was given budesonide nasal spray (20 μL once), twice a day, and the interventions were continued for 12 days. The AR rat behavioral scoring criteria was used to evaluate rhinitis behavior of rats; Morris water maze test was used to evaluate learning and memory function of rats; enzyme-linked immunosorbent assay (ELISA) was used to detect serum levels of immunoglobulin E (IgE) and transforming growth factor-β1 (TGF-β1); hematoxylin-eosin (HE) staining was used to observe pathological changes of nasal mucosa and eosinophil (EOS) count; immunohistochemistry method was used to detect expression levels of non-receptor tyrosine kinases Fyn, substance P (SP), vasoactive intestinal peptide (VIP) and neuropeptide Y (NPY) in the hippocampus; and real-time polymerase chain reaction (RT-PCR) was used to detect mRNA transcription levels of Fyn, SP, VIP and NPY in the hippocampus.Results(1) Behavioral scores of rhinitis: compared with the normal group, behavioral scores of rhinitis were significantly higher in the model group, the traditional Chinese medicine group and the western medicine group before treatment (P<0.05). Compared with the model group, behavioral scores of rhinitis were significantly lower in the traditional Chinese medicine group and the western medicine group after treatment (P<0.05). Compared with that before treatment, behavioral scores of rhinitis were significantly lower in the traditional Chinese medicine group and the model group after treatment (P<0.05). (2) Learning and memory function: compared with the normal group, the model group showed significantly longer platform latency and the total distance of swimming, as well as lower platform crossing frequency and shorter stay time in the target quadrant (P<0.05); compared with the model group, both the traditional Chinese medicine group and the western medicine group showed significantly shorter platform latency and total distance of swimming, and more times of platform crossing and longer stay in the target quadrant (P<0.05). (3) IgE and TGF-β1 contents in serum: compared with the normal group, IgE and TGF-β1 contents in serum were significantly higher in the model group (P<0.05). Compared with the model group, IgE and TGF-β1 contents in serum in both the traditional Chinese medicine group and the western medicine group were significantly lower (P<0.05). (4) Pathological changes of nasal mucosa and EOS counts: the nasal mucosa in the model group was edematous and the epithelial cells were arranged in disorder; the nasal mucosa edema were alleviated significantly in the traditional Chinese medicine group and the western medicine group after treatment, and the epithelial cell structure was more intact. Compared with the normal group, the nasal mucosal EOS counts all significantly increased in the model group, the traditional Chinese medicine group and the western medicine group after treatment (P<0.05); compared with the model group, the nasal mucosa EOS counts decreased significantly in the traditional Chinese medicine group and the western medicine group after treatment (P<0.05). (5) mRNA transcription levels and protein expression levels of Fyn, SP, VIP and NPY in hippocampus: compared with the normal group, mRNA transcription levels of Fyn, SP and VIP and average OD values of Fyn, SP and VIP increased significantly in the hippocampus in the model group (P<0.05), while mRNA transcription levels of NPY and average OD values of NPY decreased significantly (P<0.05). Compared with the model group, mRNA transcription levels of Fyn, SP and VIP and average OD values of Fyn, SP and VIP in the hippocampus decreased significantly in the traditional Chinese medicine group and the western medicine group after treatment (P<0.05), while mRNA transcription levels of NPY and average OD values of NPY increased significantly (P<0.05).ConclusionXingbi gel nasal drops can improve the behavioral scores of rhinitis and learning and memory functions of rats with AR, which may be related to the regulation of nasal mucosa-hippocampus neuroimmune mechanism through the Fyn signaling pathway.